Meningkatkan Jiwa Leadership Siswa SMA Muhammadiyah 8 Ciputat dalam Manajemen Perencanaan Berwirausaha - Endang Susilo Wardani; Oki Iqbal Khair; Reza Octovian; Diana Riana Harjayanti; Nelwati Tanius (Indonesian Journal of Society Engagement, 2022)
The main problem, which is commonly faced is the concerns in running an entrepreneur and the lack of leadership spirit that grows in the student environment. We try to motivate and provide counseling that the spirit of leadership needs to be grown and nurtured early on, especially in entrepreneurship.  Let us not be afraid to start but seize the opportunities that exist accompanied by strong intentions. Strong desire can be the driving force of our start in entrepreneurship Is expected by providing counseling to improve the Spirit of Leadership of Muhammadiyah 8 High School students. Ciputat in the management of entrepreneurship planning can foster the spirit of leadership as well as this becomes the expected external with the implementation of this PkM.